2019
DOI: 10.1007/s11357-019-00109-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of caloric restriction on mTOR and ubiquitin-proteasome pathways in skeletal muscles

Abstract: In skeletal muscles, calorie restriction (CR) preserves muscle mass in middle-aged rats but not younger rats. The underlying mechanisms for this agespecific response are unknown. Skeletal muscle mass depends on several factors, with protein synthesis and degradation playing major roles. Therefore, the purpose of this study was to investigate whether CR affects younger and older animals differently on mTOR signaling and ubiquitin-proteasome pathway (UPP). Four-, 8-, and 16-month-old rats, with or without 40% CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 56 publications
4
25
1
3
Order By: Relevance
“…CR inhibited mTORC1 expression in the liver of BMAL1- or CRY-deficient mice but enhanced mTORC2 capability only in the liver of CRY-deficient mice [ 186 ]. CR also protected the skeletal muscle mass in middle-aged rats by regulating mTOR signaling and the ubiquitin-proteasome pathway [ 187 ]. Ten months of CR protected against neuronal loss caused by aging and injury and improved learning and memory via the mTOR pathway [ 188 ].…”
Section: Mtor Signalingmentioning
confidence: 99%
“…CR inhibited mTORC1 expression in the liver of BMAL1- or CRY-deficient mice but enhanced mTORC2 capability only in the liver of CRY-deficient mice [ 186 ]. CR also protected the skeletal muscle mass in middle-aged rats by regulating mTOR signaling and the ubiquitin-proteasome pathway [ 187 ]. Ten months of CR protected against neuronal loss caused by aging and injury and improved learning and memory via the mTOR pathway [ 188 ].…”
Section: Mtor Signalingmentioning
confidence: 99%
“…However, iron metabolism is not the only player affecting muscle performance. Due to the complexity of muscle physiology, other factors can have a decisive influence on skeletal muscle, such as age, lipotoxicity, muscle stiffness, and the role of caloric restriction in muscle health [ 54 , 55 , 56 ]. In this way, sarcopenia is the age-associated loss of muscle mass and function.…”
Section: Potential Application and Future Prospects Of Black Peppementioning
confidence: 99%
“…Moreover, histopathological muscle changes as a result of the pathways triggered by sarcopenia, which affect muscle performance, are changes in muscle fiber size and number, causing mass muscle reduction with age and selective atrophy of muscle fibers [ 54 , 56 ]. In addition, another factor to consider in performance and muscle function is caloric restriction (CR) [ 55 ]. CR-induced effects are related to aging in skeletal muscle.…”
Section: Potential Application and Future Prospects Of Black Peppementioning
confidence: 99%
See 1 more Smart Citation
“…As a family of stress-induced proteins, Sestrins are involved in the maintenance of cellular homeostasis, as well as in tumorigenesis by regulating various downstream molecules of mTOR signaling pathway ( Wang et al, 2019 ). Emerging studies have shown that mTOR-associated pathways are closely related to cell growth and metabolism in different human disorders, including cancers ( Chen et al, 2019 ; Chung et al, 2019 ; Garcia et al, 2019 ). l -Leucine is an amino acid that plays an important role in the protein synthesis ( Vago et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%